TrueTales View-Manual: A tool to visualize life course data using the scientific use files of the National Educational Panel Study NEPS, starting cohort 6 - adults - Ralf Künster (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
TrueTales View is an application to visualize life courses. The tool accomplishes this in two different ways: individual life courses are displayed as bar charts and aggregated life courses are plotted as state distribution charts. The article describes the functionality and the options of TrueTales View using the example of the life course data of NEPS starting cohort 6 (adults).
Keywords: 330